Research on Roof Cutting Pressure Relief of the Gob-Side Entry Retaining With Roadside Backfilling - Zhang, Kun; Liu, Changyou; Zhang, Hanrui; Yue, Xin; Liu, Huaidong (Frontiers in Earth Science, 2022)
Based on the application of retained gob-side entry in fully-mechanized face E2307 headgate, the stress distribution and deformation characteristics of roadside backfill body for different roof cutting was investigated in this paper by employing a combination method of theoretical analysis , numerical simulation and field measurement. The study uses the Rocklab software to accurately modify the lithology of the simulation area, discuss the position of the roof cutting and the pressure relief parameters of the roof cutting, and select the optimal solution of the roof cutting plan. The results show that the advanced pre-cracking effectively cuts off the stress transmission in the high-level roof strata, the roadway is in the stress unloading zone, the stress environment of the surrounding rock in the roadway is significantly optimized, and the deformation of the surrounding rock in the roadway is significantly reduced. In the roof cutting scheme, the deformation of the surrounding rock in the 90° main roof cutting scheme is reduced by 78% compared with the uncut roof, and by 39% compared with the 90° immediate roof roofing. The research results were successfully applied at E2307 headgate of Gaohe Coal Mine, the maximum roof subsidence and the maximum rib convergence were 121 mm and 74 mm, respectively. Field monitoring indicates that the deformation of the retained entry was controllable, and the final retaining effects were good.